Differential Grainy head binding correlates with variation in chromatin structure and gene expression in Drosophila melanogaster - Ertl, Henry A.; Hill, Mark S.; Wittkopp, Patricia J. (BMC genomics, 2022)
Phenotypic evolution is often caused by variation in gene expression resulting from altered gene regulatory mechanisms. Genetic variation affecting chromatin remodeling has been identified as a potential source of variable gene expression; however, the roles of specific chromatin remodeling factors remain unclear. Here, we address this knowledge gap by examining the relationship between variation in gene expression, variation in chromatin structure, and variation in binding of the pioneer factor Grainy head between imaginal wing discs of two divergent strains of Drosophila melanogaster and their F 1 hybrid. We find that (1) variation in Grainy head binding is mostly due to sequence changes that act in cis but are located outside of the canonical Grainy head binding motif, (2) variation in Grainy head binding correlates with changes in chromatin accessibility, and (3) this variation in chromatin accessibility, coupled with variation in Grainy head binding, correlates with variation in gene expression in some cases but not others. Interactions among these three molecular layers is complex, but these results suggest that genetic variation affecting the binding of pioneer factors contributes to variation in chromatin remodeling and the evolution of gene expression.